Reactor based Voltage Regulators for Single Wire Earth Return Systems - Wolfs, Peter; Senini, S.; Hosseinzadeh, N.; Seyoum, D.; Loveday, A.; Turner, J. (Victoria University, 2006)
Single wire earth return systems, (SWER), are the lowest cost technology for rural power distribution and have global application. Voltage regulation is the determining factor for system capacity for long SWER systems. In long systems, directly connected shunt reactors are often used to compensate the effects of line to ground capacitance. The replacement of fixed shunt reactors with controllable reactors provides an opportunity to significantly increase the system capacity. Three methods of reactor control are studied. Thyristor controlled reactors or mechanically switched reactors can be connected via transformers. Alternatively, switched reactors can be connected to consumer transformers. A case study based on the North Jericho system shows the approaches capable of effecting capacity increases ranging from 82% to 100%.